Analysis of Policy Strategies To Control The Conversion Of Wetland Rice Land To Non-Agricultural Land Use In Palembang City South Sumatra - Nila Yuliantina; Andy Mulyana; Elisa Wildayana; Andries Lionardo; Betaria Septiana (Sriwijaya Journal of Environment)
Land conversion is an activity that changes the land area and also its function into a new area and has another function and has an impact on environmental problems and land potential. The impact of land conversion is the loss of rice fields and causes rice production to decline. Therefore, it is very relevant to analyze the policy strategy of agricultural land conversion to support the control of agricultural land conversion in Palembang City. This research was conducted in Palembang City in 2023 using survey method, with purposive sampling of 23 key informants. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) was used to answer this research. The results showed aggressive strategies that can be applied to control the conversion of lebak swamp land in Palembang City, namely, maintaining the level of rice productivity along with high demand, accelerating the preparation of Regional Regulations related to Sustainable Food Agricultural Land (LP2B), improving the performance of agricultural extension institutions to supervise and provide counseling, increasing the competitiveness of farmers given the existing potential and creating innovations with superior agricultural product centers in local business development-based areas.